PELATIHAN DAN PENDAMPINGAN BRANDING KEMASAN, PEMASARAN PRODUK SERTA SOSIALISASI PIRT PRODUK NISAN DAN OLUO KHAS DESA PULAU BELIMBING KECAMATAN KUOK KABUPATEN KAMPAR - Yunita, Imelda (COMMENT: Journal of Community Empowerment, 2023)
The community service activities are aimed at providing training and support for branding of packaging as well as socialization of PIRT licenses for the entrepreneurs of nisan and oluo products which are local food products of the village of Pulau Belimbing, Kuok district of Kampar. The packaging process begins with the socialization of packaging, the selection of the right packaging for nisan and oluo products as well as the design of product packaging. The socialization of products through social media is followed by the socialisation of PIRT licenses for nisan and oluo products. The public service activities have been carried out well according to the indicators of availability that socialization participants are enthusiastic about the support given and actively ask about the socialization material given. This accompaniment and socialization provides benefits for participants to be applied so that it can enhance product development and reach broader marketing.